The role of employee motivation in promoting basic health care services : a case study of Department of Health, Greater Tzaneen Subdistrict, Limpopo Province - Sekgobela, Mohwagabo Ignatius (My University, 2023)
The Limpopo Department of Health (LDoH), particularly Greater Tzaneen Sub-district, as an organ of state is mandated to promote basic health care services to community members. In order to realise this obligation, clinics were built in communities with the purpose of improving access to the basic health care services. The development and implementation of 24 hours policy, building of nurses home, security provision and introduction of call system were designed to promote basic health care services during throughout the day. Despite the measures put in place, Greater Tzaneen Sub-district has a problem of rendering 24 hours services. Basically, Greater Tzaneen Primary Health Care is faced with the challenge of not achieving the departmental goals due to the fact that some of the health care facilities are not effective in the provision of health care services. This situation is exacerbated by the low morale of health care professionals due to poor incentives and rewards. In this regard, the study attempts to investigate the role of motivation on employees in the Department of Health, particularly, at Greater Tzaneen Sub-district. The study employed qualitative research method in order to solicit data to answer the study’s question for achievement of study objectives. The study found that employees were motivated by performance incentives and rewards especially for the employees who performed 24 hours services in the selected sub-district. The study also found that employees were motivated by the quality of infrastructure development and staff accommodation. The flexible working hours were found to be enhancing the motivation of employees in the Department of Health. The study further suggested strategies to enhance motivation of employees. These strategies include salary increase, performance incentives, and better working environment, suitable infrastructure which include staff accommodation, adequate and necessary working equipment and efficient systems. Additional human resources should be recruited in order to ensure that there is fair workload for all health workers at different health care facilities
Thesis (MPAM.) -- University of Limpopo, 2023
Keywords: Employee motivation; Limpopo Department of Health; Basic health services; Job enrichment; Employee motivation -- South Africa; Employee competitive behavior; Public health -- South Africa -- Limpopo